The Influence of the Cooperative Learning Model Talking Stick Type Charged Science Literacy on Students Learning Competencies in the Material of Human Digestive Systems in SMP Negeri 15 Padang - Fitri Handayani; Rahmawati Darussyamsu; Ganda Hijrah Selaras; Syamsurizal Syamsurizal (ATRIUM PENDIDIKAN BIOLOGI, 2019)
Research on the problems that exist in Padang 15 Public Middle School, student learning competencies are still low. The effort that can be done is to apply the cooperative learning model with the speaking stick type with literacy content of SMP 18 Padang. The purpose of this study was to study student learning through a cooperative model of speaking stick type with literacy at SMP 15 Padang. This type of research is experimental research with randomized posttest control group design. The population in this study were all students of class VIII SMP 15 Padang registered in 2018/2019. Sampling was done using the Simple purposive Sampling technique, which was chosen as the research sample was class VIII.3 as the experimental class and VIII.2 as the control class. The instrument used consisted of posttest questions for knowledge competencies, observation sheets for competencies and skills. The assessment hypothesis using the t-test, can prove the knowledge competency  tcount 2.27> ttable 1.67, competency assessment value 80% with good categories and competency skills value tcount 3.5> ttable 1.67). This is an accepted hypothesis. It was concluded that the cooperative model of speaking stick type with literacy opposed the competence of knowledge, attitudes, and skills of class VIII students of SMP 15 Padang.